THE EFFECT OF THE IMPLEMENTATION OF MEDICAL SELF-GOVERNMENT ON THE CONTINUOUS DEVELOPMENT OF MEDICAL EMPLOYEES - Olieinikova, Tamara (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to analyze the impact of the introduction of medical self-governance on the continuous professional development of medical workers in Ukraine, highlighting this process as a key aspect of reforming the health care system. Research methods: documentary analysis, generalization of legal information. Results: the article analyzes the impact of the introduction of medical self-governance on the continuous professional development of medical workers in Ukraine, highlighting this process as a key aspect of reforming the health care system. In the context of international practices and the internal need for change, medical self-governance is proposed as an effective mechanism for involving physicians in the management of the industry, which allows them to directly influence the standards and practices of medical activity. The reform is aimed at the transition from an administrative model of management to a model based on professional self-regulation and self-organization, should ensure the improvement of the quality of medical services, as well as open new opportunities for the professional development of personnel. A detailed analysis of the Draft Law on Medical Self-Government No. 10388 dated 01.01.2024 and the Draft Law on Medical Self-Government No. 10372-1 dated 08.01.2024 concerning medical self-governance was also carried out, considering them in the context of current needs and trends in the medical field. Measures to implement the principles of self-governance include the creation of medical associations that bring together specialists in various fields and support continuous learning through certification and educational programs. This process includes the activation of professional organizations that play a role in the creation of training programs, certification courses and other initiatives aimed at the continuous improvement of the qualifications of doctors. Thus, doctors get the opportunity to improve their skills in accordance with the current needs and challenges of modern medicine, which directly affects the quality of medical care and the improvement of health care standards. Discussion: emphasis is placed on the importance of medical self-governance for strengthening professional autonomy and ethical standards, which, in turn, will contribute to the improvement of medical care for the population. The article also examines potential challenges and barriers to implementing this system, including the need to coordinate legislative initiatives and administrative support.